2016
DOI: 10.1002/2016jc011841
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variability of the Arctic sea ice: A comparison between AO-FVCOM and observations

Abstract: A high‐resolution (up to 2 km), unstructured‐grid, fully ice‐sea coupled Arctic Ocean Finite‐Volume Community Ocean Model (AO‐FVCOM) was used to simulate the sea ice in the Arctic over the period 1978–2014. The spatial‐varying horizontal model resolution was designed to better resolve both topographic and baroclinic dynamics scales over the Arctic slope and narrow straits. The model‐simulated sea ice was in good agreement with available observed sea ice extent, concentration, drift velocity and thickness, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The driving forces included tidal forcing with eight major constituents (M2, S2, N2, K2, K1, P1, O1, and Q1), surface wind stress, net heat flux at the surface plus shortwave irradiance in the water column, surface air pressure gradients, precipitation (P) minus evaporation (E), and river discharges. We conducted a detailed validation and comparison of the AO-FVCOM sea ice thickness data with the Arctic multisource sea ice thickness data, including ICESat-2 satellite data, field drill-hole observations, airborne electromagnetic observations, and sea ice station data (Zhang et al, 2016b). The results revealed that the sea ice thickness data of the AO-FVCOM well captured the spatial distribution, as well as seasonal and interannual variation characteristics, of Arctic sea ice thickness data.…”
Section: Simulated Sea Ice Thickness Datamentioning
confidence: 95%
See 1 more Smart Citation
“…The driving forces included tidal forcing with eight major constituents (M2, S2, N2, K2, K1, P1, O1, and Q1), surface wind stress, net heat flux at the surface plus shortwave irradiance in the water column, surface air pressure gradients, precipitation (P) minus evaporation (E), and river discharges. We conducted a detailed validation and comparison of the AO-FVCOM sea ice thickness data with the Arctic multisource sea ice thickness data, including ICESat-2 satellite data, field drill-hole observations, airborne electromagnetic observations, and sea ice station data (Zhang et al, 2016b). The results revealed that the sea ice thickness data of the AO-FVCOM well captured the spatial distribution, as well as seasonal and interannual variation characteristics, of Arctic sea ice thickness data.…”
Section: Simulated Sea Ice Thickness Datamentioning
confidence: 95%
“…Sea ice conditions exert a dominant impact on ship navigation in the NWP. As a result of global warming, coverage by Arctic sea ice is significantly decreasing (Parkinson and Comiso, 2013;Zhang et al, 2016b) and the sea ice thickness is also diminishing (Kwok et al, 2009;Lindsay and Schweiger, 2015). In particular, the Arctic sea ice extent and area dropped to historic lows of 3.4 × 10 6 km 2 and 3.0 × 10 6 km 2 on 13 September 2012 (Parkinson and Comiso, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Global‐FVCOM was driven by astronomical tidal forcing with eight constituents (M 2 , S 2 , N 2 , K 2 , K 1 , P 1 , O 1 , and Q 1 ), surface wind stress, net heat flux at the surface plus shortwave irradiance in the water column, surface air pressure gradients, precipitation minus evaporation, and river discharge at 766 river mouth locations. Supported by the International Center for Marine Studies (ICMS) at Shanghai Ocean University (SHOU), the Global‐FVCOM was validated for 50‐year spin‐up validation experiments and a 40‐year hindcast with assimilation from 1978 to 2017 (C. Chen et al, 2009, 2016; Gao et al, 2011; Zhang, Chen, Beardsley, Gao, Lai, et al, 2016; Zhang, Chen, Beardsley, Gao, Qi, et al, 2016). We also repeated the simulation experiment by using the fields of h m and Ttrue¯oml calculated from the Hybrid Coordinate Ocean Model (HYCOM) hindcast data set (HYCOM.org , 2013) (see Figures 2b and 2d).…”
Section: The Model Experiments Designs and Datamentioning
confidence: 99%
“…The driving forces included tidal forcing with eight major constituents (M2, S2, N2, K2, K1, P1, O1, and Q1), surface wind stress, net heat flux at the surface plus shortwave irradiance in the water column, surface air pressure gradients, precipitation (P) minus evaporation (E), and river discharges. We conducted a detailed validation and comparison of the AO-FVCOM sea ice thickness data with the Arctic multisource sea ice thickness data, including ICESat-2 satellite data, field drill-hole observations, airborne electromagnetic 95 observations, and sea ice station data (Zhang et al, 2016b). The results revealed that the sea ice thickness data of the AO-FVCOM well captured the spatial distribution, as well as seasonal and interannual variation characteristics, of Arctic sea ice thickness data.…”
mentioning
confidence: 94%
“…The simulated sea ice thickness data were from the Arctic Ocean-Finite Volume Community Ocean Model (AO-FVCOM) (Chen et al, 2009;Chen et al, 2016;Gao et al, 2011;Zhang et al, 2016a;Zhang et al, 2016b) for the period 1979-2017, with a horizontal resolution as high as 1 km in the CAA. These high-resolution data could be used to study the spatial distribution, as well as the seasonal and long-term variation characteristics, of sea ice thickness in the NWP.…”
mentioning
confidence: 99%